On Leverage, Uncertainty and ESG - EL FARISSI , Inass; AMCHAAROU , Houda; AYACHE , Basma (Revue Internationale des Sciences de Gestion, 2026)
This article examines how economic uncertainty and ESG performance jointly shape corporate capital structure decisions. These dimensions are typically studied separately, focusing either on uncertainty and leverage or on ESG and financing conditions, while their interaction remains underexplored. A systematic literature review (SLR) is conducted using 27 Scopus-indexed articles (2020–2025), complemented by key theoretical contributions. The analysis is structured around three dimensions: capital structure and uncertainty, capital structure and ESG, and ESG and uncertainty. The findings show that uncertainty generally leads firms to adopt more conservative financing strategies, although the effect varies depending on firm characteristics and uncertainty type. ESG performance improves financing conditions by reducing information asymmetry, but its effectiveness depends on credibility and institutional context. The study develops an integrated framework linking uncertainty, ESG, and capital structure, highlighting the need for dynamic and context-dependent corporate financing models.